The Early Childhood Education and Care system for children aged 0-6: regulatory pathway and pedagogical considerations - Silva, Clara (Form@re - Open Journal per la formazione in rete, 2018)
This article reconstructs the pedagogical and political debate that has led in Italy to the institution of an integrated Early Childhood Education and Care system, for children from birth to 6 years of age. It then examines two fundamental issues posed by the establishment of a 0-6 integrated ECEC system: a) that one related to the pedagogical profile able to unify two paths – namely, the “nido” (an ECEC service for children from 0 to 3 years of age), and the “scuola dell’infanzia” (an ECEC service for the age group 3-6), both born and developed in a disjoint way, until today; b) that one connected to the matter of how the L-19 University graduation class, officially appointed to the initial training of ECEC educators, could offer a training proposal consistent with Early Childhood educators’ career opportunities. Il sistema di educazione dell’infanzia 0-6: percorso normativo e riflessioni pedagogiche Il presente contributo ricostruisce nelle linee generali il dibattito pedagogico e politico che ha portato all’istituzione in Italia del sistema di educazione e cura dell’infanzia dalla nascita a sei anni. Esamina poi due questioni fondamentali poste dall’istituzione del sistema integrato zero-sei: a) quella relativa al profilo pedagogico capace di rendere unitari due percorsi, l’uno del nido e l’altro della scuola dell’infanzia, nati in maniera disgiunta e proseguiti in maniera parallela fino ad oggi; b) come la classe di laurea L-19, ufficialmente deputata alla formazione iniziale degli educatori, possa offrire una proposta formativa coerente con gli sbocchi professionali dell’educatore per la prima infanzia.